2017
DOI: 10.3168/jds.2017-13200
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the level and duration of maternal diets with negative dietary cation-anion differences prepartum on calf growth, immunity, and mineral and energy metabolism

Abstract: The objectives were to investigate the effects that maternal diets containing negative dietary cation-anion differences (DCAD) fed in the last 42 d of gestation may have on the acid-base status, hematology, mineral and energy metabolism, growth, and health of calves. The experiment was a randomized block design with a 2 × 2 factorial arrangement of 2 levels of negative DCAD (-70 or -180 mEq/kg) and 2 feeding durations (the last 21 d prepartum and the last 42 d prepartum). Bulls and heifers (n = 60) born to the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
5

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(40 citation statements)
references
References 35 publications
7
28
5
Order By: Relevance
“…However, Morrill et al (2010) reported similar concentrations of serum IgG and apparent efficiency of absorption in calves born to dams fed diets with or without anionic salts prepartum. Collazos et al (2017) did not observe any difference in serum IgG or IgG apparent efficiency of IgG absorption of calves born to cows fed diets with −7 or −18 mEq/100 g of DM DCAD. Results from our current trial suggest that there was no effect of DCAD on the apparent efficiency of IgG absorption in calves based on serum IgG concentrations after feeding 200 g of IgG from a colostrum replacer.…”
Section: Short Communicationmentioning
confidence: 54%
See 1 more Smart Citation
“…However, Morrill et al (2010) reported similar concentrations of serum IgG and apparent efficiency of absorption in calves born to dams fed diets with or without anionic salts prepartum. Collazos et al (2017) did not observe any difference in serum IgG or IgG apparent efficiency of IgG absorption of calves born to cows fed diets with −7 or −18 mEq/100 g of DM DCAD. Results from our current trial suggest that there was no effect of DCAD on the apparent efficiency of IgG absorption in calves based on serum IgG concentrations after feeding 200 g of IgG from a colostrum replacer.…”
Section: Short Communicationmentioning
confidence: 54%
“…However, others have reported negative effects on IgG absorption in calves whose dam were fed negative DCAD diets (Joyce and Sanchez, 1994;Guy et al, 1996;Quigley and Drewry, 1998). More recently, Collazos et al (2017) reported a transient metabolic acidosis in calves born to dams fed acidogenic diets prepartum. The objectives of this trial were to determine the effects of prepartum DCAD and dietary Ca concentration on colostrum quality, newborn calf blood minerals, and gas concentration.…”
Section: Short Communicationmentioning
confidence: 99%
“…Maternal acid‐base balance during pregnancy is associated with fetal development (Collazos et al . ). Very small changes in pH may affect the function of fetal organ systems (Omo‐Aghoja, ).…”
Section: Discussionmentioning
confidence: 97%
“…In cows, a negative dietary cation‐anion difference in maternal diet affected growth and energy metabolism in the calves (Collazos et al . ). In our study, there was no difference in maternal plasma pH, PnormalCO2, Na + , Cl − , HCO 3 − or osmolality between dietary groups; however, maternal plasma PnormalO2 was significantly increased in the rats fed the HLA diet.…”
Section: Discussionmentioning
confidence: 97%
“…Recently, attention was given to the interaction of DCAD with calcium (Ca) concentration [11], cholecalciferol/calcidiol [12], 5-hydroxy-l-tryptophan [13], vitamin D [14][15][16], and duration [17,18] of blood Ca level increases. Results of these studies indicated that lower DCAD in association with the above factors was effective in improving homeostasis of peripheral blood Ca.…”
Section: Introductionmentioning
confidence: 99%